Consumer Boredom: Boredom as a Subliminal Mood of Consumer Capitalism - Mariusz Finkielsztein (European Journal of American Studies)
The article poses the thesis that boredom is the main driving force of the consumer capitalist system. Through a sequence of social and cultural shifts and freeloading on natural human predispositions, the system has manufactured a new type of being, homo consumens, who is socialized to be passive, desire- and dream-driven, and addicted to novelty, constant change, a ceaseless stream of stimuli, and pleasure. Boredom enables a smooth functioning of such a system. Bored consumers buy more and are led by desires that promise to alleviate their boredom. Consumer capitalism is devoted to the fighting of the very boredom that it actively produces, amplifies, or invites in consumer socialization. The entire entertainment/culture industry is, in fact, the boredom industry, whose institutions are preoccupied with mitigating the consumers’ situational boredom, but—at the same time—push this light type of boredom into the subliminal realm, where it has time to accumulate and takes root unnoticed, becoming a subliminal mood of consumer capitalism.